Perancangan Desain Interaksi Aplikasi Malang Sehat Modul Pendataan dan Monitoring Kesehatan Masyarakat Kota Malang dengan menggunakan Metode Human-Centered Design - Rifda Syahdatina; Herman Tolle; Hanifah Muslimah Az-Zahra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
According to the Law No. 36 of 2009 concerning Health, the government is obliged to provide access to information, education, and health service facilities to the public. One effort that can be done by the government is to present health data to the public so that they can educate and increase the awareness regarding the importance of maintaining a healthy lifestyle. Along with efforts to develop the smart city concept, Dinkes together with Kominfo, has provided health data through Malang City health profile and Malang City Open Data site. However, the data displayed is difficult for the public to understand. Therefore, it is necessary to devise an interaction design for the development of information systems based on a mobile app to make it more flexible and convenient for users to access. The design process in this study was carried out by applying the Human-Centered Design, which focuses on users and stakeholders. In the evaluation process, testing was carried out using the Remote Usability Testing technique by 21 evaluators and using the System Usability Scale questionnaire. The results of this test are a percentage value of 92% in the aspect of effectiveness and 91% in the aspect of efficiency. In the aspect of satisfaction, the value obtained is 75.71 with the title 'Acceptable' and get a C grade included in the 'Good' category of adjective ratings.